Opportunities for Leadership Expression in a Learning Organization - Šneiderienė, Agnė; Vaitiekus, Antanas; Vaitiekienė, Janina (Socialiniai tyrimai, 2020)
The creation and development of an information and knowledge-based society and knowledge economy are perceived as one of the most important priorities of social, economic, political development, culture, science and technological progress of modern society (Melnikas, Jakubavičius, Leichteris and Stumbrytė, 2017). It is important to create a learning society, a learning organization, a knowledge economy in order to adapt to the various challenges. Tortorella, Vergara, Garza-Reyes and Sahney (2020) noted that organizational learning can be seen as a process of improvement based on a clearer understanding and knowledge directly related to the organizational culture and environment. The scientific literature (Sakalas, 2012; Walker, 2014; Atkočiūnienė, 2014; Skrickienė, Čepuraitė and Štaras, 2018) presents various features of learning organization characteristics: strategy development, investment in one’s future, cooperation, environmental monitoring, focusing on problem identification and resolution, processing and applying large flows of information, responding, and anticipating internal and external changes. Organizational learning is a way of survival, capacity building, enabling it to change, that is to cope with change, and seize new opportunities. According to Walker (2014), knowledge, learning, and innovation are the key factors assuring the success of a modern organization. It should be noted that the acquisition, use and recognition of knowledge largely depend on the culture of the organization. As Salge and Vera (2012) argued, learning organizations understand the importance of learning and increase the ability to turn new knowledge into tangible improvements. In the scientific literature (Minelgaitė and Vaičiukynaitė, 2017; Katilienė, 2010; Vilkaitė-Vaitonė, Papšienė and Stulgienė, 2016; Digrienė, 2018; Shao, Feng and Hu, 2017; Walker, 2014) various definitions, styles and models of leadership have been identified. Usually, many definitions of leadership highlight one aspect in relation to other aspects (Minelgaitė and Vaičiukynaitė, 2017). Amor, Vázquez and Faíña (2020) noted that leadership is a critical component influencing an organization’s environment and how employees perceive their work. It should be noted that leadership theory is very diverse, but in the context of a learning organization, the types of transformational and transactional, empowering, positive, and collective leadership are important. It should be emphasized that the leader in the organization of the 21st century must be able to mobilize the organization’s staff for the implementation of strategic tasks; to be able rationally and effectively form a favourable environment for the learning organization. Managers and top managers must be guided by modern imperatives of a complex nature: the ideology of innovation, the perception of the need and necessity of change and reform, the application of best practices and experience of postmodern management in their organizational structures. Ewa, Cox, Tse and Lowe (2019) noted that there is a growing number of organizations that prosper and in which leadership is shared rather than concentrated in the hands of specific individuals or between these individuals. The importance of collective leadership will only increase as organizations involve more organizational, virtual, and non-traditional teams. Thus, there will be a need for a smoother and more dynamic process of empowering and consolidating leadership roles. Thus, it is very important to assess what are the opportunities for leadership expression in a learning organization. The object of research is the possibilities of leadership in a learning organization. The aim of the article is to form a model for determining the possibilities of leadership expression in a learning organization. To achieve the goal, the following tasks are formulated: 1. Analyse the definitions and features of a learning organization. 2. Examine the concept of leadership and analyse leadership styles. 3. Identify opportunities for leadership expression in a learning organization. 4. Form a model for determining the possibilities of leadership expression in a learning organization. Methods of analysis, descriptive, analytical and comparative analysis of scientific literature are applied in the article. The members of the learning organization are constantly improving their skills, raising their competence, improving their activities based on experience, and improving their decision-making skills. Organizational learning can be ensured through knowledge acquisition, information distribution, information interpretation, and organizational memory. The learning organization must ensure the existence of the following elements: systemic thinking, personal mastery, management of mental models, development of a shared vision and team learning. There is a link between a learning organization and the existence of increased organizational innovation capacity, increased productivity and competitive advantage. It should be emphasized that in order to be successful, it is necessary to exchange knowledge, communicate and learn, clarify and change existing practices. Leadership theory is very diverse, but in the context of a learning organization, transformational and transactional leadership systems become particularly evident. Types of empowering, shared, positive, collective leadership are also distinguished. Leadership can be viewed as any activity that relies on an individual’s abilities to effectively play a leadership role in an organization. Leadership development involves the social capital required to lead at the collective or individual level. Leadership can be expressed through the leadership style of leaders, the level of feedback, and the granting of autonomy to subordinates. Learning organizations need knowledgeable, motivated, self-confident employees who can generate new knowledge, make decisions about the acquisition and use of knowledge. Leaders’ participation in decision-making allows followers to share their ideas and collaborate, which in turn encourages effective knowledge flows. Inclusive and shared leadership approaches are essential to ensure more sustainable organizational change through forms of organizational learning. There are three social dimensions that facilitate the creation of a learning organization: psychological safety, participation in decision-making, and openness to different opinions. The links between learning organization and leadership can be assessed through organizational culture, personal and collective values, honesty, trust, and collaboration. The possibilities of leadership expression in a learning organization are associated with various variables: the leader, followers, and the conditions that determine the constant changes in the organization. Opportunities for the expression of leadership in a learning organization are possible in various activities of the organization, but it should be emphasized a necessity to form a learning friendly environment, i.e. ensuring psychological security, openness to opinions, participation in the decision-making process. By creating a favourable environment, employees will be more motivated to participate in both the individual and collective learning process, will supplement, share and create new knowledge in order to achieve the efficiency of the organization.